2022
DOI: 10.1007/s11740-022-01164-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving the wear resistance of copper tools for pressure die casting by laser melt injection

Abstract: Highly conductive copper alloys are used for various tools in casting and welding technology. In pressure die casting, copper alloys are used for pistons pressing the metal melt into a die. The high thermal conductivity of these alloys allows short process times as a result of high cooling rates. Due to a poor wear resistance, wear occurs on the running surface of the pistons causing the metal melt to spurt out of the shot sleeve. In order to improve the service life of the pistons, a new approach was taken: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Copper-filled PLA specimen showed one of the highest COF values which is attributed to low wear resistance and high ductility. 54 Lower COF values are recorded in the wet sliding test of copper-filled PLA specimen which can be attributed to good ductility properties and absence of pulled off particles in the wear medium. Bronze-filled PLA specimen had moderate COF value compared to other filler materials in the dry sliding condition.…”
Section: Coefficient Of Frictionmentioning
confidence: 90%
“…Copper-filled PLA specimen showed one of the highest COF values which is attributed to low wear resistance and high ductility. 54 Lower COF values are recorded in the wet sliding test of copper-filled PLA specimen which can be attributed to good ductility properties and absence of pulled off particles in the wear medium. Bronze-filled PLA specimen had moderate COF value compared to other filler materials in the dry sliding condition.…”
Section: Coefficient Of Frictionmentioning
confidence: 90%
“…In contrast, the residual strains and stresses in the Cu matrix of the sFTC/bronze composite deposit and the re‐melted bronze samples were measured via neutron diffraction at the beamline SALSA, Institut Laue‐Langevin. [ 17 ] The neutron wavelength was 1.644 Å with the Si (400) monochromator. The gauge volumes for the longitudinal, transversal, and normal directions are 0.6 × 2.0 (//Y) × 0.6, 10.0 (//X) × 0.6 × 0.6, and 10.0 (//X) × 0.6 × 0.6 mm 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…LMI is therefore beneficial for a variety of wearexposed tool surfaces, such as casting tools and injection molds, which are often made of copper alloys. LMI with fused tungsten carbide (FTC) particles in the copper alloy Hovadur® CNCS led to a significant improvement in wear resistance against the hardened and gas nitrided steel 1.2343 [2]. Tribological tests for an aluminum bronze and FTC MMC have shown that wear can be reduced by 76% [3].…”
Section: Introductionmentioning
confidence: 99%